Harapan Bajulmati Educational Institution As Role Model For Interfaith Harmony In South Malang - Edy Sutrisno (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2020)
Education is a very appropriate tool, especially in using dynamic and inclusive religious values for everyone in society. Educational institutions are the main basis for shaping religious values in creating harmony between religious communities, therefore the model of harmony between religious communities can be applied in various community contexts. The purpose of this paper is to determine the Harapan Bajulmati educational institution as a role model for harmony between religious communities in South Malang. While the method in this writing uses descriptive qualitative methods. The results of this study are a role model of harmony between religious communities with education through educational institutions as the main basis for developing models of harmony between religious communities by means of a humanist and persuasive approach. Pendidikan menjadi sarana yang sangat tepat, khususnya di dalam menggunakan nilai-nilai agama yang dinamis dan inklusif bagi setiap orang yang berada dalam masyarakat. Lembaga pendidikan merupakan dasar utama dalam membentuk nilai-nilai agama dalam menciptakan kerukunan antar umat beragama oleh karena itu model kerukunan antar umat beragama bisa diterapakan dalam konteks masyarakat yang beragam. Tujuan dalam penulisan ini adalah untuk mengetahui lembaga pendidikan Harapan Bajulmati sebagai role model kerukunan antar umat beragama di Malang Selatan. Sedangkan metode dalam penulisan ini menggunakan metode kualitatif deskriptif. Adapun hasil dalam penelitian ini adalah role model kerukunan antar umat beragama dengan edukasi melalui lembaga pendidikan sebagai basis utama dalam mengembangkan model kerukukunan antar umat beragama dengan cara pendekatan humanis dan persuatif.